Epistemic Contextualism: An Idle Hypothesis. Issue 1 (2nd January 2017) - Turri, John
ABSTRACT: Epistemic contextualism is one of the most hotly debated topics in contemporary epistemology. Contextualists claim that 'know' is a context-sensitive verb associated with different evidential standards in different contexts. Contextualists motivate their view based on a set of behavioural claims. In this paper, I show that several of these behavioural claims are false. I also show that contextualist test cases suffer from a critical confound, which derives from people's tendency to defer to speakers' statements about their own mental states. My evidence consists in results from several behavioural experiments. I conclude that contextualism is an idle hypothesis and I propose some general methodological lessons.